Meronymy as a Lexical Cohesion Device in the Film Final Destination: Bloodlines: A Discourse Analysis - Harris Ramadhan; Zia Hisni Mubarak (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examines the use of meronymy as a form of lexical cohesion in the dialogue of the film Final Destination: Bloodlines, based on Paltridge’s (2022) theory of lexical cohesion. The study aims to identify the types of meronymic relations found in the dialogue and to explain their role in maintaining coherence of meaning in audiovisual discourse. A qualitative descriptive approach was employed, with data collected through documentation by observing and transcribing the film dialogue. The data were analyzed by identifying utterances that contain part–whole relationships and interpreting their functions within the context of the scenes. The findings reveal seven instances of meronymy, which are realized through references to body parts, parts of buildings, and institutional elements. These meronymic expressions are predominantly found in scenes involving danger, injury, and critical situations. The analysis shows that meronymy functions not only to clarify specific references but also to connect smaller linguistic units to broader narrative contexts, thereby supporting coherence in dialogue. This study demonstrates that meronymy plays a strategic role in organizing meaning and enhancing the continuity of discourse in film dialogue. It contributes to the understanding of lexical cohesion in audiovisual texts by highlighting how part–whole relationships help construct meaning in context.